Entre a trama e a urdidura : complexidade no (e do) significado da fisioterapia - Ely, Jaqueline Colombo (2011)
Influenced by modern science, professional practice in health care seems to limit the possibility to close in on them as therapists, realities and issues increasingly multidimensional and contextual as a way of inculcating knowledge and practice often insufficient. The physiotherapy treatment is a problem of utmost importance - for the profession of physiotherapy and to individuals who have experienced it - once enmeshed, in essence, a multi-tissue problems inseparable. This is a case study, descriptive in nature. Women participating in this study were residents of the long-term institution Nossa Senhora da Luz in Passo Fundo - RS and held weekly sessions of physiotherapy. Using the proposed interpretative sieve as the complexity of Edgar Morin, we understand the significance of physical therapy for three women institutionalized in the physical therapy treatment. The content analysis technique was used for data analysis. Understanding the meaning of physiotherapy we identified multidimensionality constituent, representative references and discontinuities: a multiplicity unclear, contradictory, complementary, relational, and the interrelation in (and of) meaning of physiotherapy. We believe that the many complex, uncertain, contradictory, complementary, relational and interrelation of the meaning and constitutive of the meaning of physiotherapy were coming from, especially the vulnerability of the current condition of women institutionalized and built the space of empathy between researcher and researched